Active immunization with an octa-valent Staphylococcus aureus antigen mixture in models of S. aureus bacteremia and skin infection in mice. - Sanne van den Berg; Dennis G A M Koedijk; Jaap Willem Back; Jolanda Neef; Annette Dreisbach; Jan Maarten van Dijl; Irma A J M Bakker-Woudenberg; Girbe Buist (PLoS ONE, 2015)
Proteomic studies with different Staphylococcus aureus isolates have shown that the cell surface-exposed and secreted proteins IsaA, LytM, Nuc, the propeptide of Atl (pro-Atl) and four phenol-soluble modulins α (PSMα) are invariantly produced by this pathogen. Therefore the present study was aimed at investigating whether these proteins can be used for active immunization against S. aureus infection in mouse models of bacteremia and skin infection. To this end, recombinant His-tagged fusions of IsaA, LytM, Nuc and pro-Atl were isolated from Lactococcus lactis or Escherichia coli, while the PSMα1-4 peptides were chemically synthesized. Importantly, patients colonized by S. aureus showed significant immunoglobulin G (IgG) responses against all eight antigens. BALB/cBYJ mice were immunized subcutaneously with a mixture of the antigens at day one (5 μg each), and boosted twice (25 μg of each antigen) with 28 days interval. This resulted in high IgG responses against all antigens although the response against pro-Atl was around one log lower compared to the other antigens. Compared to placebo-immunized mice, immunization with the octa-valent antigen mixture did not reduce the S. aureus isolate P load in blood, lungs, spleen, liver, and kidneys in a bacteremia model in which the animals were challenged for 14 days with a primary load of 3 × 10(5) CFU. Discomfort scores and animal survival rates over 14 days did not differ between immunized mice and placebo-immunized mice upon bacteremia with S. aureus USA300 (6 × 10(5) CFU). In addition, this immunization did not reduce the S. aureus isolate P load in mice with skin infection. These results show that the target antigens are immunogenic in both humans and mice, but in the used animal models do not result in protection against S. aureus infection.